The Effect of a Training Program in Developing Young Soccer Players’ Accuracy and Endurance of Scoring Skill Performance - Mahmoud, Sadiq Jaafer (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to verify the effect of a training program on developing the young soccer player’s accuracy and endurance for scoring skill performance. It also aims to verify the statistical differences in the accuracy and endurance of scoring skill performance between the pre and post tests of the individuals of the research sample. To verify the research objectives, the researcher hypothesized that there are statistically significant differences between the pre and post tests results in the accuracy and endurance of scoring performance. The researcher made use of the experimental approach to make the nature of the research more appropriate. The experiment was carried out on 34 players of the Youth Sport Club for Soccer (17-19 years) for season (2019-2020). These players were intentionally chosen. Uniformity was achieved among the members of the research sample in the variable covered by the research, which is accuracy and endurance of scoring performance in soccer. The experimental design was adopted in the style of a single group with a pre-post test, namely; accuracy and endurance of the scoring performance in football. The experimental design was adopted in the style of one group with a pre and post test. The researcher used (SPSS) for statistical treatments coming up with key conclusions that the training program achieved an improvement in the accuracy and endurance of scoring performance by comparing the results of the pre-post test for the individuals of the research sample. The researcher recommends using the training program in the accuracy and endurance of young soccer player’s scoring skill performance.